Cognitive therapy and eye movement desensitization and reprocessing for reducing psychopathology among disaster-bereaved individuals: study protocol for a randomized controlled trial. Issue 1 (1st January 2017) - Lenferink, Lonneke I. M.; Piersma, Eline; de Keijser, Jos; Smid, Geert E.; Boelen, Paul A.
ABSTRACT: Background : Confrontation with a traumatic (e.g. disaster-related) loss is a risk factor for the development of psychopathology, including symptoms of prolonged grief (PG), posttraumatic stress (PTS), and depression. Although interventions have been developed for reducing post-loss psychopathology, more research into the effectiveness of treatment is needed to improve care for bereaved persons. Cognitive therapy (CT) and eye movement desensitization and reprocessing (EMDR) have been shown to be effective in trauma-exposed populations. We hypothesize that CT and EMDR are also effective in reducing symptoms among people exposed to traumatic loss. Objective : In this article we describe the rationale of a randomized controlled trial (RCT) to examine (1) treatment effects of CT and EMDR for reducing PG, PTS, and depression among traumatically bereaved people, and (2) the associations between improvements in PG, PTS, and depression symptoms on the one hand and tentative mechanisms of change, including a sense of unrealness, negative cognitions, avoidance behaviour, and intrusive memories, on the other hand. Method : A two-armed (intervention versus waiting list controls) RCT will be conducted. Participants will be asked to fill in questionnaires prior to treatment, during treatment, and one, 12, and 24 weeks post-treatment. Potential participants are people who have lost one or multiple significant other(s) in the Ukrainian plane disaster in 2014 with clinically significant levels of self-rated PG, PTS, and/or depression. Multiple regression, including analysis of covariance, and multilevel regression analyses will be used. Discussion : There is a need for treatment for psychopathology following traumatic loss. Strengths of this study are the development of a treatment that targets grief and trauma-related complaints and the examination of potential mechanisms of change in CT and EMDR. Bereaved people, clinicians, and researchers could benefit from the results of this study.